BENTUK DAN VARIASI KUBUR MEGALITIK DI PEGUNUNGAN SELATAN JAWA - Muhammad Hidayat (Balai Arkeologi Yogyakarta, 2008)
Megalithic is one of cultures based on religious concept. This particular concept had entered and developed sporadically in various regions in Indonesia for long time. Eventhough they were based on a same concept, but each had been expressed differently. One of them is represented by the burial mode. There are three kinds of burial mode in South Mountain, Java. Stone cist found at Gunungkidul, kubur watu tumpuk and kubur menhir at Wonogiri. Environment is one of many factors affected those different burial modes.